Clinical Utility of Circulating Tumor DNA in Advanced Rare Cancers - Okuma, Hitomi Sumiyoshi; Yonemori, Kan; Kojima, Yuki; Tanioka, Maki; Sudo, Kazuki; Noguchi, Emi; Hijioka, Susumu; Wakakuwa, Keiko; Kato, Ken; Hirakawa, Akihiro; Kuchiba, Aya; Kubo, Takashi; et al. (Frontiers in Oncology, 2021)
Purpose Patients with advanced/relapsed rare cancers have few treatment options. Analysis of circulating tumor DNA in plasma may identify actionable genomic biomarkers using a non-invasive approach. Patients and Methods Rare cancer patients underwent prospective plasma-based NGS testing. Tissue NGS to test concordance was also conducted. Plasma DNA alterations were assessed for incidence, functional impact, therapeutic implications, correlation to survival, and comparison with tissue NGS. Results Ninety-eight patients were analyzed. Diseases included soft-tissue sarcoma, ovarian carcinoma, and others. Mean turn-around-time for results was 9.5 days. Seventy-six patients had detectable gene alterations in plasma, with a median of 2.8 alterations/patient. Sixty patients had a likely pathogenic alteration. Five received matched-therapy based on plasma NGS results. Two developed known resistance mutations while on targeted therapy. Patients with an alteration having VAF ≥5% had a significantly shorter survival compared to those of lower VAF. Tissue NGS results from eleven of 22 patients showed complete or partial concordance with plasma NGS. Conclusion Plasma NGS testing is less invasive and capable of identifying alterations in advanced rare cancers in a clinically meaningful timeframe. It should be further studied as a prospective enrollment assay in interventional studies for patients with rare advanced stage cancers. Clinical Registration [https://www.umin.ac.jp/ctr/index-j.htm], identifier UMIN000034394.